The clinical significance of low complement levels in patients with catastrophic antiphospholipid syndrome: A descriptive analysis of 73 patients from the "Catastrophic antiphospholipid syndrome registry". (September 2022) - Ponce, Ana; Rodríguez-Pintó, Ignasi; Basauli, José M; Espinosa, Gerard; Erkan, Doruk; Shoenfeld, Yehuda; Cervera, Ricard
Objectives: To explore the prevalence and clinical significance of low complement levels in patients with catastrophic antiphospholipid syndrome (CAPS). Methods: We reviewed data from the "CAPS Registry" on C3 and/or C4 complement plasma protein levels during acute CAPS episodes. Patients were classified into those with low and normal complement levels. Data on clinical presentation, with special focus on thrombotic microangiopathy (TMA) features, diagnosis of systemic lupus erythematosus (SLE), and antiphospholipid antibody (aPL) profile were reviewed. The chi-square exact test was performed to evaluate differences between categorical data. Results: The "CAPS Registry" includes 566 patients with a total of 578 episodes of CAPS. Data on complement plasma protein levels was available in 73 episodes from the same number of patients. Low levels of C3 and/or C4 complement plasma proteins were detected in 42 (58%) CAPS episodes. Low complement levels were more common in SLE patients (55% SLE vs. 19% No SLE; p<0.001). The frequencies of clinical TMA (72% vs. 80%; p=0.4) or TMA syndrome (86% vs. 84%, p=0.9), frequency of triple aPL triple positivity (67% vs 33%; p=0.3), or the mortality (35% vs. 31%; p=0.7) were similar between low and normal complement groups. Conclusion: In our study, low levels of C3 and C4 plasma proteins are detected in 58% episodes of CAPS, which were not associated with clinical presentation including TMA features, aPL triple positivity, or mortality.